Theoretical approach of a polymer stabilized blue phase beam steering - Algorri, Jose Francisco; Urruchi, Virginia; Bennis, Noureddine; Sanchez-Pena, Jose Manuel (Photonics Letters of Poland, 2017)
Nematic liquid crystal (LC)-based beam steering has been reported for wide applications. However, for conventional nematic LC beam steering the thickness is of several microns in order to have a wider deflection angle. The response time is relatively slow and the diffraction efficiency is low. In this work, novel beam steering based on polymer stabilized blue phase liquid crystal (PS-BPLC) has been designed and theoretically analyzed. This special mesophase of the chiral doped nematic LC has several advantageous characteristics, for example no need for alignment layers, microsecond response time and an isotropic voltage-off state. The results reveal control over phase retardation. The direction of the steered beam can be tuned by voltage. Depending on voltage configuration, either diffractive beam steering (0.5deg deviation for 1st order) or a tunable continuous phase (tunable deviation of 0.002deg) can be obtained. In the first case, the deflection angle could be tuned by stacks of samples. The second option has the same phase shift for the TE and TM modes so unpolarized light could be used. Full Text: PDF References F. Feng, I. White, T. Wilkinson, "Free Space Communications With Beam Steering a Two-Electrode Tapered Laser Diode Using Liquid-Crystal SLM", J. Lightwave Technol. 31, 2001 (2013). CrossRef E. Oton, J. Perez-Fernandez, D. Lopez-Molina, X. Quintana, J.M. Oton, M.A. Geday, "Reliability of Liquid Crystals in Space Photonics", IEEE Photonics Journal 7, 1 (2015). CrossRef J. Stockley, S. Serati, "Multi-access laser terminal using liquid crystal beam steering", IEEE in Aerospace Conference, 1972 (2005). CrossRef D. Zografopoulos and E. Kriezis, "Switchable beam steering with zenithal bistable liquid-crystal blazed gratings", Opt. Lett. 39, 5842 (2014). CrossRef Benedikt Scherger, et al., "Discrete Terahertz Beam Steering with an Electrically Controlled Liquid Crystal Device", J. Infrared. Millim. Terahertz Waves 33, 1117 (2012). CrossRef M.A. Geday, X. Quintana, E. Otón, B. Cerrolaza, D. Lopez, F. Garcia de Quiro, I. Manolis, A. Short, Proc. ICSO, Rhodes, Greece, pp. 1-4 (2010). CrossRef Y. Chen, S.-T. Wu, "The outlook for blue-phase LCDs", Proc. SPIE 9005, Advances in Display Technologies IV, 900508 (2014). CrossRef G.D. Love, A.F. Naumov, "Modal liquid crystal lenses", Liq. Cryst. Today 10, 1 (2000). CrossRef V. Urruchi, J.F. Algorri, J.M. Sánchez-Pena, M.A. Geday, X. Quintana, N. Bennis, "Lenticular Arrays Based on Liquid Crystals", Opto-Electron. Rev. 20, 38 (2012). CrossRef J.F. Algorri, G. Love, and V. Urruchi, "Modal liquid crystal array of optical elements", Opt. Express 21, 24809 (2013). CrossRef J.F. Algorri, V. Urruchi, N. Bennis, J. Sánchez-Pena, "Modal liquid crystal microaxicon array", Opt. Lett. 39, 3476 (2014). CrossRef J.F. Algorri, V. Urruchi, B. Garcia-Camara, J.M. Sánchez-Pena, "Generation of Optical Vortices by an Ideal Liquid Crystal Spiral Phase Plate", IEEE Elect. Dev. Lett. 35, 856 (2014). CrossRef D. Xu, Y. Chen, Y. Liu, S. Wu, "Refraction effect in an in-plane-switching blue phase liquid crystal cell", Opt. Express 21, 24721 (2013). CrossRef Z. Ge, S. Gauza, M. Jiao, H. Xianyu, S.T. Wu, "Electro-optics of polymer-stabilized blue phase liquid crystal displays", Appl. Phys. Lett. 94 101104 (2009). CrossRef J. Yan et al., "Extended Kerr effect of polymer-stabilized blue-phase liquid crystals", Appl. Phys. Lett. 96, 071105 (2010). CrossRef X. Wang, D. Wilson, R. Muller, P. Maker, D. Psaltis, "Liquid-crystal blazed-grating beam deflector, Appl. Opt. 39, 6545 (2000). CrossRef